PENEGAKAN HUKUM DAN PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PENCABULAN - Sihombing, Windah Shindy; Petrus Irwan Panjaitan; Radisman Saragih (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The crime of obscenity is one of the crimes in the sexual field that is very disturbing to the community, this is also contrary to the Government's goal to create a safe, peaceful and prosperous society. Therefore, the authors are interested in conducting research to find out how law enforcement and criminal responsibility of children against children as perpetrators of criminal acts of sexual abuse are based on the Decision of the East Jakarta District Court Number 18/Pid.Sus- Anak/2020/Pn.Jkt.Tim. So specifically that regulates law enforcement and accountability for criminal acts of sexual harassment against minors, there are regulations that regulate it apart from the Criminal Code (KUHP), namely Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The formulation of the problem in this thesis is about law enforcement and criminal responsibility for children as perpetrators of criminal acts of obscenity. The author uses two theories, namely Law Enforcement Theory and Responsibility Theory. Using normative legal research methods. Legal materials are sourced from primary data and secondary data.